Education Development Perspective: The Influence of Family Environment on Educational Motivation of Buddhist Youth - Laras Puspita Sari; Juni sur; Burmansah bur; Mega Julianti; Tejo Ismoyo; Dedi Kundana; Eko Pramono (Universitas Sebelas Maret, 2024)
The family environment is the first place of education for children because this is where children first receive education and guidance. The research purpose is to explore the influence of the family environment on the motivation of the Buddhist youth in Buddhist Temples throughout Pringsewu Regency in Lmapung Province. The problems faced include low educational motivation allegedly influenced by lack of family support, economic factors, and ineffective communication. The study developed the quantitative method and survey data collection tecnique with a questionnaire and supported by SPSS program This study involved a population of 87 number of people. This study's results show a significant influence of the family environment on educational motivation. These findings show that family support is essential in increasing the motivation of young people in monasteries.